Information asymmetry and the problem of transfers in trade negotiations and international agencies - Koichi Hamada; Shyam Sunder (Yale University, Economic Growth Center, 2005)
This paper studies the role of transfers among groups within a country as well as among countries in a two level game of international trade negotiations. We show that in order to realize the intended transfer in the presence of asymmetric information on the states of recipients (and donors), a transfer process uses up additional resources. The difficulty of making transfers renders it less likely that a nation would find it individually rational to participate as a member of an international institution. Costly transfers render the internal and international adjustment difficult, and serve as a barrier to trade liberalization. Costly international transfers harden the resistance against trade liberalization in the (potentially) recipient country and soften it in the (potentially) donor country.
Keywords: O82; F13; H21; H71; H77; 330; International trade; tariff negotiation; asymmetric information; transfer; WTO; common agency; two-level game